2021
DOI: 10.3390/foods10112711
|View full text |Cite
|
Sign up to set email alerts
|

Apple Polyphenols Extract (APE) Alleviated Dextran Sulfate Sodium Induced Acute Ulcerative Colitis and Accompanying Neuroinflammation via Inhibition of Apoptosis and Pyroptosis

Abstract: The main aim of this study was to investigate the potent anti-apoptosis and anti-pyroptosis effects of apple polyphenols extract (APE) on dextran sulfate sodium model group (DSS)-induced acute ulcerative colitis (UC) and the protective effect of APE against acute UC-related neuroinflammation and synapse damage. Forty-three C57BL/6 male mice were randomly divided into a control group (CON), a 3% DSS model group (DSS), a 500 mg/(kg·bw·d) APE group (HAP), and a 125 (LD) or 500 (HD) mg/(kg·bw·d) APE treatment conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Based on the immunofluorescence analysis, a reduced protein level of IBα1 in the hippocampus and cortex was found after APE intervention. Meanwhile, our previous study also confirmed the alleviated depression and anxiety in acute colitis mice after APE intervention by reducing the mRNA expression of Cox-2 and GFAP in mouse brain tissue . Therefore, APE intervention ameliorated HFCD-induced atherosclerotic neuroinflammation in LDLR –/– mice.…”
Section: Discussionsupporting
confidence: 58%
“…Based on the immunofluorescence analysis, a reduced protein level of IBα1 in the hippocampus and cortex was found after APE intervention. Meanwhile, our previous study also confirmed the alleviated depression and anxiety in acute colitis mice after APE intervention by reducing the mRNA expression of Cox-2 and GFAP in mouse brain tissue . Therefore, APE intervention ameliorated HFCD-induced atherosclerotic neuroinflammation in LDLR –/– mice.…”
Section: Discussionsupporting
confidence: 58%
“…In conclusion, AP, the main secondary metabolites extracted [16][17][18] Therefore, AP possesses a good prospect for the development of anti-UC health food and drugs. It is believed that with the continuous development of research, AP would achieve promising results in clinical treatment.…”
Section: Discussionmentioning
confidence: 90%
“…15) However, as far as we know, there are not many related reports on AP treatment for UC. [16][17][18] Caco-2 cells, which could mimic human intestinal epithelial cells in the body when cultured in monolayer, have been widely used as a typical in vitro UC model for antioxidant study. [19][20][21][22] Hydrogen peroxide (H 2 O 2 ) which is an important ROS, could induce the oxidative stress damage and apoptosis of many cells.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there is little research about effect of plant polyphenols especially PCA or Que on pyroptosis signals. Only Liu et al reported that apple polyphenols extract ameliorated dextran sulfate sodium-induced acute ulcerative colitis through inhibiting intestinal epithelial cell apoptosis and pyroptosis pathway [62]. Luo et al reported that Que possessed a protective effect on macrophages pyroptosis via TLR2/Myd88/ NF-ΚB pathway [63].…”
Section: Discussionmentioning
confidence: 99%